Homologasi Penundaan Kewajiban Pembayaran Utang (PKPU) Sebagai Upaya Preventif Terjadinya Pailit : Studi Putusan Mahkamah Agung No.137K/Pdt.Sus-PKPU/2014 - Maranatha Purba; Sunarmi Sunarmi; Bismar Nasution; Keizerina Devi (USU LAW JOURNAL, 2019)
Abstract. Homologation is the endorsement by the judge of the peace agreement between the debtor by the creditor to end the bankruptcy. Peace (akkoord) in phases this phase is PKPU is most important, because in the debtor will offer peace plan peace were to creditors. The possible existence of peace in the restructuring of debts the debtor. If peace is approved by the creditors, then the PKPU by-law will end. Peace is one of legal efforts to resist he did bankruptcy against the debtor. Peace in the process of bankruptcy is often referred to with the term "accord" (Netherlands) or in the language of the United Kingdom referred to by the term "Composition". Talking about peace in bankruptcy do not only exist in the bankruptcy process, but there are also in the process of debt payment suspension (PKPU). Peace is one of the ways to end the bankruptcy. Peace can be used as a tool to force it does because of the debt restructuring outside of bankruptcy. the lender (concurrent) cannot be forced to agree to peace. peace is defined as an agreement between the debtor and the kreditornya where the claims of the creditors agreed to partially or completely paid. Supreme Court justices in the disconnect of case No. 137 K/Pdt. Sus-PKPU/2014 is just right. The parties in this ruling, namely Julia Tjandra and Jerry Farolan as creditors and PT Djakarta Lloyd has obtained legal certainty, namely repayment bills have got a fixed legal power, got a guarantee so that the debtor does not cheat and benefit for the debtor is still given a chance to manage again and his effort to prevent the debtor from possible mass execution by kreditor-kreditornya in order for the continuity of the business. Keywords: Homologation, PKPU, Bankruptcy